Peripheral and Intracranial Compartment Serum Level of Selenium in Pediatric Patients with Intracranial Tumor in Department of Neurosurgery, Faculty of Medicine, Universitas Padjadjaran–Dr. Hasan Sadikin Hospital, Bandung, Indonesia: a Preliminary Study and Literature Review - Ahmad Faried; Priandana Adya Eka Saputra; Mirna Sobana; Muhammad Zafrullah Arifin (Faculty of Medicine Universitas Padjadjaran, 2016)
Objective: To determine the level of Selenium (Se) in peripheral and intracranial serum in pediatric patients with intracranial tumor. Selenium has chemopreventive potentials and acts as neuromodulator.Methods: This study was conducted on 13 pediatric patients with intracranial tumors who were treated in Dr. Hasan Sadikin Hospital, Bandung in the period of February 2014 to February 2015. Samples were taken from peripheral and intracranial serum. The results were analyzed with independent t-test and Pearson correlation test. Significance is defined as p≤0.05 with 95% confidence interval.Results: The results showed that the average Se concentration in peripheral serum was significantly higher than the Se concentration in intracranial serum (95.92±20.95 μg/L and 66.62±22.37 μg/L, respectively). After classifying the subjects into groups based on sex, age, tumor location, and grades, the difference between Se concentrations were still statistically significant (p≤0.05), with the exception of the supratentorial group (p=0.0053). Pearson correlation test showed very-low to medium strength correlations between peripheral and intracranial serum Se concentration in all groups (r=0.16–0.59, p>0.05).Conclusions: A significant difference is seen between the peripheral and intracranial serum Se concentration means in pediatric patients with intracranial tumors, with higher concentrations observed in the peripheral serum. Further studies are required to investigate the roles of Se in the management of pediatric patients with intracranial tumors.Keywords: Pediatric intracranial tumor patients, selenium concentration in peripheral and intracranial serum DOI: 10.15850/ijihs.v4n2.835